Solow meets Marx: Economic growth and the emergence of social class - Jørgen Heibø Modalsli (University of Oslo, Department of Economics, 2011)
This paper reconciles neoclassical models of economic growth (Solow) with the formation of social classes during economic transition (Marx). An environment with missing capital markets and no labor divisibility is shown to lead to a steady state with no aggregate inefficiencies, but a very polarized wealth distribution. When capital cannot be rented, people must choose between self-production, potentially including hiring workers, and wage employment. As the first path is more profitable for the rich than the poor, inequality increases. The model is calibrated to illustrate polarization and increasing inequality in early modern Europe, starting from a continuous pre-industrial wealth distribution. During the early industrializing period, when labor markets operate and capital markets do not, inequality increases and a distinct working class emerges. Even if capital markets later improve, the polarization is persistent. The mechanism also has relevance for modern developing countries, where capital market access is limited. If a substantial amount of capital is needed in order to earn the market return, the poor have few incentives to save.
Keywords: O11; E21; O43; G32; 330; Inequality; polarization; social class; economic growth; capital market frictions; Wachstumstheorie; Soziale Ungleichheit; Vermögensverteilung; Soziale Schicht; Finanzmarkt